Spinal cord perfusion pressure protocol for acute spinal cord injury: Pragmatic implementation and early results at two sites - John Paul G. Kolcun; Ricky M. Ditzel Jr; Bradley L. Kolb; Ricardo B. V. Fontes; P. B. Raksin (PLoS ONE, 2026)
Study design Retrospective chart review. Objective Describe safety/feasibility of implementing a novel clinical protocol for acute spinal cord injury (SCI) management. Summary of background data Spinal cord perfusion pressure (SCPP) has emerged as a promising target for the medical management of SCI patients. We report our early experience implementing a pragmatic SCPP-driven clinical protocol to supplant conventional mean arterial pressure (MAP) monitoring in the setting of acute SCI. Methods We retrospectively reviewed charts of all SCI patients managed by our SCPP protocol since its adoption at two clinical sites as of 2/1/2023. The SCPP protocol was applied for all adult SCI patients of any injury grade, at any injury level with cord tissue involvement. Intrathecal pressure (ITP) was transduced by lumbar drain (LD). MAP was determined from invasive blood pressure recordings. SCPP was calculated as the difference between MAP and ITP, with an SCPP goal of >65mmHg. Results Eighteen patients have been treated since our SCPP protocol was adopted. Patients were predominately male (77.8%); the average age was 52.0 ± 16.2 years. Most injuries involved the cervical segment (72.2%), all of which were manifest clinically as central cord syndrome. The most common presenting injury severity was ASIA Impairment Scale D (44.4%). All patients underwent surgical intervention. There were no complications related to surgery, LD placement, or LD maintenance/ITP transduction during hospitalization. The SCPP protocol was continued for an average 5.2 ± 1.8 days. Eight patients required vasopressor support (44.4%) during that period, for an average 3.1 ± 2.1 days. Five patients underwent therapeutic CSF drainage to augment SCPP (27.8%). All patients maintained an average SCPP above goal for the duration of monitoring. Conclusions This study further establishes the safety and feasibility of monitoring SCPP via LD measurement of ITP in acute SCI patients treated by clinical protocol at two clinical sites. There were no complications related to LD placement/maintenance or SCPP monitoring.